(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the frequency of papilledema and radiological signs of increased intracranial pressure (ICP) in our cohort of migraineurs, and investigate the possible clinical predictors.Material and Methods: This was a cross-sectional study in which we have included all the patients with migraine who applied to our neurology clinic during January 2020 and accepted to involve in the study. The demographic and clinical characteristics including migraine subtype (episodic/chronic), headache frequency per month, headache characteristics were evaluated in all the study group. Besides, the presence of chronic fatigue syndrome (CFS) was noted. The fundus examination was performed in all the patients. Previously defined eight findings of increased ICP were evaluated by our radiologist. We have classified the migraineurs into two groups as migraineurs with clinical suspicion of increased ICP and those without. We have identified the patients with papilledema and/or positivity of at least one of the neuroimaging signs of increased ICP as migraineurs with suspicion of increased ICP. The remaining patients were defined as migraineurs without suspicion of increased ICP. Results: Ultimately, 63 migraineurs were included in this study. The median age was 36.8 ± 11.3 and the F/M ratio was 51/12. Papilledema was determined in 11 (17.4%) of the patients and 19 (30.1%) of the migraineurs had at least one of the neuroimaging signs of increased ICP. Twenty-six (41.3%) of the overall group were evaluated as migraineurs with suspicion of increased ICP and 37 of the patients were those without suspicion of increased ICP. The comparisons between these two patient groups revealed that obesity was more prevalent in the migraineurs with suspicion of increased ICP. Logistic regression analyses revealed obesity (OR: 0.090, P = 0.014) and radicular pain (OR: 7,647, P = 0.030) as clinical predictor factors for the patients with suspicion of increased ICP. Conclusion: We determined a high rate of patients with either a positive neuroimaging sign of increased ICP and/or papilledema in our cohort of migraineurs. Our results may suggest obesity and radicular as potential risk factors in the prediction of increased ICP in migraineurs. The results of this study need to be confirmed in future prospective-studies with the evaluations of the lumbar puncture opening pressures in the patient subgroup with required indication.